Acceptability of GM foods among Pakistani consumers - Ali, Akhter (GM Crops Food, 2016)
In Pakistan majority of the consumers do not have information about genetically modified (GM) foods. In developing countries particularly in Pakistan few studies have focused on consumers' acceptability about GM foods. Using comprehensive primary dataset collected from 320 consumers in 2013 from Pakistan, this study analyzes the determinants of consumers' acceptability of GM foods. The data was analyzed by employing the bivariate probit model and censored least absolute deviation (CLAD) models. The empirical results indicated that urban consumers are more aware of GM foods compared to rural consumers. The acceptance of GM foods was more among females' consumers as compared to male consumers. In addition, the older consumers were more willing to accept GM food compared to young consumers. The acceptability of GM foods was also higher among wealthier households. Low price is the key factor leading to the acceptability of GM foods. The acceptability of the GM foods also reduces the risks among Pakistani consumers.